Suppression of low-frequency vibration for rotor-bearing system of flywheel energy storage system. (15th April 2019) - Qiu, Yujiang; Jiang, Shuyun
Highlights: Two types of new magnetic pendulum TMD's were developed to suppress the low-frequency vibration of the FESS. Dynamic model for the rotor-bearing system of FESS was established by using the Lagrange's equation. Design strategy of the magnetic pendulum TMD was verified by test study with a 100-class FESS. Identification method of dynamic parameters for the magnetic pendulum TMD was proposed. Abstract: A nonsynchronous low-frequency whirling occurs frequently for flywheel energy storage system (FESS) with permanent magnetic bearing (PMB) and spiral groove bearing. To suppress low-frequency vibration of a large-mass FESS, a radial magnetic pendulum tuned mass damper (TMD) and an axial magnetic pendulum TMD have been developed; and identification method of dynamic parameter for the magnetic pendulum TMD has been proposed. Dynamic model for the FESS has been established using the Lagrange's equation; and effectiveness of the two magnetic pendulum TMD's has been evaluated by analyzing mode damping ratios of the FESS. The results show that the two TMD's can be effective for the low-frequency vibration of the high-capacity FESS with PMB and spiral groove bearing; and radial magnetic pendulum TMD is superior to the axial magnetic pendulum TMD due to its lower resonant frequency and larger mode damping ratio for the FESS.